Guerre du droit, droit de la guerre - Anne-Sophie Chambost; Alexandra Gottely (Revue d’Histoire des Sciences Humaines)
Components of a French society drawn into the First World War, law faculties were first affected through their cohorts of mobilized students and staff (both academical and administrative). They also had to adjust their organisation, to meet the needs of wartime. But most of all, they were actively committed to what would soon be named the War of the Right. United behind its Dean Ferdinand Larnaude, Paris Law Faculty and its library are an excellent vantage point to observe the multiple commitments of higher learning institutions in the Great War.